Kounis syndrome: from an unexpected case in the Emergency Room to a review of the literature. - Poggiali, Erika; Benedetti, Irene; Vertemati, Valeria; Rossi, Luca; Monello, Alberto; Giovini, Manuela; Magnacavallo, Andrea; Vercelli, Andrea (Acta Biomedica Atenei Parmensis, 2022)
Kounis syndrome (KS) is a coronary syndrome in the setting of allergic/anaphylactic reactions and can be classified in three variants: vasospastic allergic angina (type I), allergic myocardial infarction (type II) and stent thrombosis (type III). The early diagnosis is of paramount importance for the correct management and the prognosis, being KS a life-threatening emergency condition. KS is not uncommon, but it is frequently unrecognized or undiagnosed in virtue of its broad clinical manifestations. The diagnosis should be based on the combination of cardiovascular and allergic/anaphylactic clinical symptoms and signs, as well as on laboratory, electrocardiographic, echocardiographic, and angiographic evidence. ECG monitoring, cardiac enzymes and troponin are mandatory to confirm or exclude KS in a patient with subclinical or clinical, acute or chronic allergic reactions. Nevertheless, the treatment is a real challenge for the emergency clinicians because guidelines have not been established yet, and the therapy is based on the variant type. We herein report the case of type I KS in a woman with no prior history of allergy, admitted to our emergency department for abdominal pain, nausea and hematochezia. Starting from this case we conducted a systematic search of the following databases: PubMed, Google Scholar, Science Direct, Medline, using the keywords of “Kounis syndrome”, “coronary spams”, “cardiac arrest”, “sudden death”, “allergy”, and “anaphylaxis”. The main purpose of this review is to remind emergency clinicians to keep a high index of suspicion regarding KS when dealing with patients with allergic reactions or anaphylaxis to promptly identify and correctly manage KS.